2021
DOI: 10.14710/ik.ijms.26.4.254-264
|View full text |Cite
|
Sign up to set email alerts
|

Producing Active Secondary Metabolite Against Pathogenic Vibrio spp. by Actinobacteria-Sodium Alginate Co-Culture

Abstract: Vibrio vulnificus, Vibrio parahaemolyticus and Vibrio harveyi have been found in aquatic environments and suspected as the primary trigger of WFD (White Feces Disease) outbreaks in aquaculture. This Vibrio spp. has an antibiotic resistance to Ampicillin, Co-Amoxiclav, Amoxicillin, Azithromycin, Actinobacteria and Ciprofloxacin HCL. Actinobacteria and alginate have been reported to increase the marine biota resistance against diseases through prebiotic and probiotic mechanisms. This study aims to discover and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Another study by Ref. [ 36 ] reported that different strains of Streptomyces sp. showed antibacterial activity against Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Ref. [ 36 ] reported that different strains of Streptomyces sp. showed antibacterial activity against Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Gentamycin (10 mcg) was taken for the antibiotic sensitivity test, which was performed for both pathogens. The Actinomycete isolate showing the maximum zone of inhibition was chosen for further study by the Kirby–Bauer agar disc diffusion method [ 36 ] to check the antibacterial activity against pathogens. In this method, the pathogens were first swabbed entirely from the surface of sterile MHA plates.…”
Section: Methodsmentioning
confidence: 99%
“…The Actinomycete isolates were determined to be within the genus Streptomyces using amplification of the 16S rRNA gene (Supplementary Table S1). The genus is distinguished by the production of a wide range of extracellular enzymes and bioactive secondary metabolites with diverse structural and functional properties that are used as antibacterial, antifungal, antiviral, antioxidant, immunomodulatory, anticancer, antibiofilm agents 12 , and anti-vibrio compounds [31][32][33][34] . Streptomyces labedae, for example, has been shown to inhibit the biofilm-forming ability of Acinetobacter and Moraxella 35 , and S. variabilis has an antibiofilm effect against the human clinical pathogens V. cholerae, Escherichia coli, and Staphylococcus aureus 36 .…”
Section: Discussionmentioning
confidence: 99%